KONSEP HUKUM PEMBATASAN KEKUASAAN REGULASI DI INDONESIA (Jurnal Magister Hukum Perspektif, 2019)
The law in limiting power lies from the formation of regulations by authorized bodies. Regulations cannot be separated from the Government / legislative institutions that make laws and regulations, both in the Central and Regional Governments. The formulation of the issues raised are (1) How is the legal concept in limiting the increasing regulation and (2) How to strive for increased harmonization so that in making regulations in the area can be in line with the existing regulations in the center. This type of research is juridical-normative using a conceptual approach. The results of the discussion are first, the legal concept in limiting the increasing regulation by applying attribution authority appropriately and making regulations according to needs. Second, efforts to increase harmonization in the making of regulations between the Center and the Regions with harmonization for quality and appropriate regulations. Keywords: legal concepts, restrictions powers, regulatory.